Wheat Microbiome: Potentiality of Alleviating Drought Stress - Al-Abbadi, Yousef Soud; Sadder, Monther Taha (South Eastern European Journal of Public Health, 2024)
Climate change is a major threat that affects global crop production. Global warming impacts crop production through abiotic stresses. Drought is one of the biggest threats to wheat cultivation. In this regard, various technologies, such as breeding programs and genetic engineering, are being applied to cope with this threat. Such methods are expensive and time-consuming. Myriad adaptive mechanisms are used by wheat plants to cope with drought stress. However, plant associations with microbiomes have gained attention lately. There is much evidence of both endopytic and rhizospheric bacteria in promoting the growth of wheat plants under drought. Their effects on plants are either by triggering direct or indirect responses to mitigate drought stress. Such responses exist at physiological, morphological, biochemical, and molecular levels. Biochemical such as the production of phytohormones, extracellular polymeric substances (EPS), siderophore, 1-aminocyclopropane-1-carboxylate (ACC) deaminase, antioxidants, osmolytes, and volatile organic compounds, in addition to solubilization of minerals and nitrogen fixation, or at molecular levels such as activation of stress genes and transcription factors. Or through many morphological and physiological responses, such as increasing relative water content (RWC) and root length and weight. Thus enhancing growth and tolerance for drought. This review highlights the potential of rhizospheric and endophytic bacteria to alleviate drought stress in wheat plants through different mechanisms, which are a sustainable and environmentally friendly way to mitigate drought.